Glandula Tiroid Problem: Literature Review - Muhammad Zaki Abdul Hafiz; Daan Khambri (Biomedical Journal of Indonesia, 2021)
Thyroid cancer is the most common endocrine system neoplas m . Based on the "Pathologycal Based Registration" in Indonesia, thyroi d cancer is a cancer with the highest incidence in the ninth rank. According to statistics from the National Cancer Institute (NCI), the incidence of thyroid cancer in men is about 2.5 per 100.000 population and women around 6.7 per 100.000 populati on. Thyroi d cancer can affect all age groups and the frequency increases afte r the age of 50 years. Only about 5% can affect the age of 15-20 years. NCI also states that this thyroid cancer can affect 16.000 people pe r year. Diagnosis is important to improve the quality of life for sufferers. Clinical diagnosis is the basis for determining furthe r management, so that knowledge and skills are needed in determining the diagnosis. The first treatment for a cancer is the best chance for the patient to achieve optimal cure rates, as is the case for thyroid cancer.